Hidden in plain sight: A rare subcutaneous tailgut cyst mimicking chronic sacrococcygeal lesions (Indian Journal of Case Reports, 2025)
Tailgut cysts (retrorectal cystic hamartomas) are rare congenital remnants of the embryonic hindgut. They typically present as deep-seated presacral masses, often diagnosed incidentally or after secondary complications. However, subcutaneous tailgut cysts are extremely rare, often leading to misdiagnosis. We report a unique case of a 37-year-old female with a chronic, painful sacrococcygeal lesion, initially misdiagnosed as a recurrent infected sinus. The case underscores the diagnostic challenges, the need to differentiate tailgut cysts from other subcutaneous lesions in this region, and the crucial role of histopathology in achieving an accurate diagnosis.